The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Femme, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques